Potential Nano Gel Avocodo Seed Extract as an Alternative Relief in Wounds After Removal of White Rats Tooth - yulistina, yulistina; Suwondo, Ari; Santoso, Bedjo (Publikasi Indonesia, 2022)
Inflammation, bleeding, swelling, pain, dry socket are common complications of tooth extraction. The inflammatory response is divided into two, including the administration of non-steroidal anti-inflammatory drugs (NSAIDs) and steroid anti-inflammatory drugs. Every use of chemical drugs has side effects. Herbal ingredients are needed, namely avocado seeds as an alternative treatment in preventing inflammation in wounds after tooth extraction. Avocado seeds contain polyphenols that play a role in inflammation in wounds, including flavonoids, alkaloids, tannins, and saponins. Experiment with randomized posttest design with control group design. Consisting of intervention group nano gel avocado seed extract 10%, positive control group povidone iodine 10% and aquadest. Observations were made for 7 days. The variables studied were inflammation of the wound after tooth extraction of rats and histopathological examination (Lymphocytes, Neocapillary and Fibroblasts). Based on the results of the unpaired test, the avocado and povidone groups were not significantly different (p=0.143), the avocado and aquadest groups had a significant difference (p=0.001) and the povidone and aquadest groups had a significant difference (p =0.015). The administration of nano gel of avocado seed extract with a concentration of 10% and 10% povidone iodine has the same ability in the process of wound regeneration and increases new blood vessels and can also reduce the number of lymphocyte inflammatory cells as evidenced by histological examination . The administration of nano gel of avocado seed extract is effective and can be applied as an alternative to prevent inflammation in wounds after tooth extraction in white rats.